Bioquímica hepática e função tireoidiana de cães hígidos tratados com prednisona - Lanis, Adriene Brêtas (2011)
Prednisone is one of the most prescribed glucocorticoid in veterinary medicine, and although it provides many positive effects, it also provides some adverse effects. The aim of this study was to evaluate in dog submitted to prednisone therapy, the occurrence of steroid hepatopathy, and the changes in hormone tests thyroid function. Eight healthy adult dogs, without gender distinction, were utilized for this. The experiment was divided into two moments, the initial moment being prior to the use of prednisone, and the following moment after 30 days of the use of prednisone. The dosage administered was 2mg for each kg, each 24 hours, orally. It was possible to conclude through serum biochemical analysis that there was significant hepatic lesion, characterized through significant increase for ALT and AST values. It is also possible conclude significant decrease for the values of T4, free T4 by dialysis (P<0.05). Thus it is recommended that the use of this drug is accompanied by laboratory monitoring.